Inclusive deep inelastic scattering at high Q2 with longitudinally polarised lepton beams at HERA - Aaron, Francisc Dionisie; Hennekemper, Eva; Krüger, Katja; Lendermann, Victor; Pirumov, Hayk; Sauter, Michel David; Schöning, André; Schultz-Coulon, Hans-Christian (Journal of high energy physics, 2012)
ABSTRACT Inclusive e ± p single and double differential cross sections for neutral and charged current deep inelastic scattering processes are measured with the H1 detector at HERA. The data were taken at a centre-of-mass energy of s√=319s=319 \sqrt {s} = {319} GeV with a total integrated luminosity of 333.7 pb−1 shared between two lepton beam charges and two longitudinal lepton polarisation modes. The differential cross sections are measured in the range of negative four-momentum transfer squared, Q 2, between 60 and 50 000 GeV2, and Bjorken x between 0.0008 and 0.65. The measurements are combined with earlier published unpolarised H1 data to improve statistical precision and used to determine the structure function xFγZ3xF3γZ xF_{3}^{{γ Z}} . Ameasurementoftheneutralcurrentparityviolating structure function FγZ2F2γZ F_{2}^{{γ Z}} is presented for the first time. The polarisation dependence of the charged current total cross section is also measured. The new measurements are well described by a next-to-leading order QCD fit based on all published H1 inclusive cross section data which are used to extract the parton distribution functions of the proton.
Gesehen am 08.11.2018
Im Titel ist die Zahl 2 hochgestellt